Numerical analysis of gas pulsation attenuation characteristics of a perforated tube in a reciprocating compressor piping system. (February 2016) - Liu, Zhan; Feng, Quanke
This paper presents a non-linear mathematical model to simulate the pulsating flow in a compressor piping system with perforated tube geometries. The governing equations are numerically solved by a composite scheme incorporating the two-step Lax–Wendroff method with the trapezoidal integration version of the method of characteristics at the pipe boundaries. The validity of the mathematical model and the methodology was verified by comparing the analytical predictions with experimental results. On basis of the confirmed model, the effects of a perforated tube on pressure pulsations in the piping system were investigated. A further investigation on the effects of the geometrical parameters and compressor functioning conditions was also conducted. The results demonstrated that pressure fluctuations at the compressor cylinder nozzle could be significantly reduced with a ratio of 53.1% when a perforated tube was installed between compressor and surge volume, but it had little influence on the pressure pulsations in the piping downstream of the surge volume. It is worth mentioning that a longer perforated tube yielded a better damping performance while the hole diameter had little effect on the pressure pulsations. The magnitude to which the perforated tube could damp the pulsations changed under different functioning conditions and the damping capacity was less sensitive to the mean pressure in the piping than to the compressor running speed.